E-cigarette adverts and children's perceptions of tobacco smoking harms: an experimental study and meta-analysis. Issue 7 (16th July 2018) - Vasiljevic, Milica; St John Wallis, Amelia; Codling, Saphsa; Couturier, Dominique-Laurent; Sutton, Stephen; Marteau, Theresa M
Abstract : Objectives: Children exposed to electronic cigarette (e-cigarette) adverts may perceive occasional tobacco smoking as less harmful than children not exposed to e-cigarette adverts. Given the potential cross-cueing effects of e-cigarette adverts on tobacco smoking, there is an urgent need to establish whether the effect found in prior research is robust and replicable using a larger sample and a stronger control condition. Design: A between-subjects experiment with one independent factor of two levels corresponding to the advertisements to which participants were exposed: glamorous adverts for e-cigarettes, or adverts for objects unrelated to smoking or vaping. Participants: English school children aged 11–16 (n=1449). Outcomes: Perceived harm of occasional smoking of one or two tobacco cigarettes was the primary outcome. Secondary outcomes included: perceived harm of regular tobacco smoking, susceptibility to tobacco smoking and perceived prevalence of tobacco smoking in young people. Perceptions of using e-cigarettes were gauged by adapting all the outcome measures used to assess perceptions of tobacco smoking. Results: Tobacco smokers and e-cigarette users were excluded from analyses (final sample n=1057). Children exposed to glamorous e-cigarette adverts perceived the harms of occasional smoking of one or two tobacco cigarettes to be lower than those in the control group ( Z =−2.13, p=0.033). An updated meta-analysis comprising three studies with 1935 children confirmed that exposure to different types of e-cigarette adverts (glamorous, healthful, flavoured, non-flavoured) lowers the perceived harm of occasional smoking of one or two tobacco cigarettes ( Z =3.21, p=0.001). Conclusions: This study adds to existing evidence that exposure to e-cigarette adverts reduces children's perceptions of the harm of occasional tobacco smoking.